Mortality caused by experimental infection with the yeast Candida haemulonii in the adults of Ornithodoros moubata (Acarina: Argasidae) - Loosová, G; Jindrák, L; Kopácek, P (Folia parasitologica, 2001)
A relatively high rate of mortality among engorged females of Ornithodoros moubata (Murray, 1877) was observed in our laboratory colony. The general aim of the study was to identify the causative agent responsible for this mortality. The diagnostic tests were performed by Yeast Identification Service (CBS-Delft, Netherlands) and the pathogen was identified as the yeast Candida haemulonii (van Uden et Kolipinski, 1962) Meyer et Yarrovi, 1978. The artificial infection study was performed by intrahaemocoelic inoculation of yeast suspension, resulting in a mortality of 37%. The maximum mortality of ticks infected per os by contaminated blood meal was 13%. Re-isolated yeast cells from haemolymph of dead and paralysed ticks were apparently identical with primary yeast cells, without loosing reproductive abilities. An occasional formation of elongated chains of yeast cells (pseudomycelium) was recorded. The majority of ticks infected in both experiments mentioned above survived and displayed no evident symptoms of the infection. The presence of yeast cells in the haemolymph of surviving ticks was not detected. The in vitro phagocytosis assay performed with FITC-labelled yeast cells showed that about 4% of tick haemocytes were phagocytically active against the pathogenic yeast cells. Thus phagocytosis seems to be a potent defence reaction against spreading and multiplying of the yeast C. haemulonii within the tick haemocoel.
Keywords: hemolymfa; Animals; Candidiasis; Female; Microscopy, Fluorescence; ženské pohlaví; interferenční mikroskopie; Hemolymph; fluorescenční mikroskopie; Microscopy, Interference; klíšťata; Ticks; biologická kontrola škůdců; fagocytóza; Phagocytosis; Pest Control, Biological; Candida; zvířata; kandidóza